Causes and criteria of disharmonies in family system functioning - Maksymova, Nataliia Yu.; Hrys, Antonina; Maksymov, Mykola V.; Krasilova, Yuliia M.; Udovenko, Julia M. (Linguistics and Culture Review, 2021)
The article highlights the problem of finding the causes of disharmonies in marital relations and the criteria for the normal functioning of a family system. Dysfunction or disturbances of family functioning are such features of family life that complicate or hinder execution of family functions. A dysfunctional family in a broad sense means a system determining distortions of personal development and, therefore, maladaptive, deviant behaviour or neurotic disorders at one or more of the family members. The aim of the study is to identify the causes of disharmony in marital relations and the criteria for normal functioning of a family as a system. The empirical part of this study was devoted to determining the causes of such disharmonies in marital relationships that subsequently led to divorce. The study was conducted during the family counselling of married men, women and married couples who were in the process of divorce. The next criteria for normal family functioning have been determined: respect for differences; sincerity in expressing thoughts and feelings; dynamic relationships; role sharing; observance of personal boundaries; family openness; emotional and spiritual intimacy.